ENTOMOLOGICAL INDEX AND INSECTICIDE SUSCEPTIBILITY STATUS IN DENGUE-ENDEMIC AREAS YOGYAKARTA - Astuti, Fardhiasih Dwi; Azka, Arlina (Epidemiology and Society Health Review (ESHR), 2021)
Backgrounds: Dengue Hemorrhagic Fever (DHF) is a disease that receives special attention because of causing outbreaks in some countries, including Indonesia. The problems that often emerge on the DHF Control Program are the high vector density (Aedes aegypti) and the vector resistance resulting from continuous insecticide use. This study describes the entomological index and susceptibility status of Aedes aegypti against malathion and permethrin insecticides in Sorosutan, Umbulharjo, Yogyakarta.Methods: This study used a descriptive observational method with a cross-sectional design. An entomological survey is done at 354 houses in Sorosutan, which is randomly selected. The sample of Aedes aegypti was obtained through the larval collection and ovitrap installation in 100 places. Susceptibility tests performed using the bioassay method with impregnated paper were based on the WHO standard. This study was conducted from December 2018 – February 2019. The data were analyzed using univariate analysisResults: The entomological survey in Sorosutan showed the House Index value was 35.03%; Container Index was 16.68%; Breteau Index was 46.33; Density Figure was 5.00, and Larva Free Rate was 64.97%; meaning that Sorosutan had a high level of vector density. So, the risk of DHF transmission was high. The population of Aedes aegypti in Sorosutan has been tolerant against Malathion, with 87.83% mosquito mortality.Conclusion: Sorosutan was an area with high DHF transmission risk. Aedes aegypti population in Sorosutan has been tolerant against Malathion.